Dynamics under Uncertainty: Modeling Simulation and Complexity - Pamučar, Dragan; Marinkovic, Dragan; Kar, Samarjit (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The dynamics of systems have proven to be very powerful tools in understanding the behavior of different natural phenomena throughout the last two centuries. However, the attributes of natural systems are observed to deviate from their classical states due to the effect of different types of uncertainties. Actually, randomness and impreciseness are the two major sources of uncertainties in natural systems. Randomness is modeled by different stochastic processes and impreciseness could be modeled by fuzzy sets, rough sets, Dempster-Shafer theory, etc.